A perspective overview on lipospheres as lipid carrier systems - Dudala, Thushara Bindu; Yalavarthi, Prasanna Raju; Vadlamudi, Harini Chowdary; Thanniru, Jyotsna; Yaga, Gowri; Mudumala, Naga Lakshmi; Pasupati, Vivek Kumar (International Journal of Pharmaceutical Investigation)
Both hydrophilic and lipophilic therapeutics can be delivered successfully into deep and peripheral tissues such as cerebrospinal fl uid and central nervous system by encapsulating them with crystalline lipids as lipospheres. The advent of lipospheres was meant to deliver both therapeutic moieties with enhanced effi cacy and added stability to reach out intended tissue areas. Although extensive information is available on physicochemical, analytical and biopharmaceutical aspects of lipospheres, there was no specifi c order pertaining to critical composition and rationale of component selection available for academic and pilot scale processing of lipospheres. With the interest of compiling key points in a typical formulation of lipid lipospheres, this article was intrigued to discuss melt method, co-solvent, microemulsion, super critical fl uid, spray drying and spray congealing techniques that were employed to scale up lipospheres. The selection criteria for both the drugs and lipids in liposphere formulations were demonstrated here. The quality assessment with variables like loading capacity and entrapment effi ciency was explained. A note on preliminary screening factors to determine the liposphere formation such as liposphere dimensions with morphological scenario was detailed in this article. This article also includes the stability and storage issues with reference to photolysis. The marked differential in enhancing solubility and permeability characteristics of Class II and IV drug candidates by liposphere delivery systems with an evident of in vivo outcomes were emphasized.
Keywords: Critical composition; entrapment effi ciency; lipids; loading capacity; morphology; stability